Integrating JSIT and Merdeka Curriculum: Case Study of Islamic Character Building at SDIT Robbani Malang - Putri, Fitria Azizah Yona; Nafiadi, Fardan Harish; Aldisa, Nabila Zahwa; Ahyani, Shidqi (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3743, 2025)
Islamic character represents the values taught in the Qur'an and Sunnah of the Prophet Muhammad SAW, which include good morals, behavior, and ethics. However, with the passage of time and technological advances, there has been a negative impact in the form of moral degradation, which can be seen from the shift in values and behavior among students. This has given rise to attitudes that are contrary to the Islamic character that we want to embody, causing students to tend towards individualism, egoism, and hedonism. This problem has become a challenge that needs to be overcome in order to restore Islamic character in the current generation. In this context, Integrated Islamic Schools, with the aim of providing character education that is relevant and adaptive to the changing times, are suitable as a forum to address this problem. Integrated Islamic Schools that adopt the JSIT curriculum as a reference in the learning process contain a form of integration from the Merdeka Curriculum. Therefore, this study aims to analyze the integration of the JSIT curriculum in the perspective of the Merdeka Curriculum, particularly in the strategy of instilling Islamic character at SDIT Robbani Malang. This study describes the integration of the JSIT curriculum in the perspective of the Merdeka Curriculum, the strategies applied in shaping Islamic character, and the Islamic character that develops in students. This study uses a qualitative approach with a case study type to explore in depth the implementation of the curriculum and pedagogical practices in a real context. SDIT Robbani was purposively selected because it actively implements the JSIT Curriculum and carries out structured Islamic character education. Data collection was conducted through observation, interviews, and documentation. The results show that the integration of the JSIT curriculum with the Merdeka curriculum converges on the vision of character education and TERPADU learning. As a manifestation of the results of this integration in instilling Islamic character, SDIT Robbani implements strategies in the form of habituation, cooperation with parents, and role modeling. Therefore, the Islamic character that emerges as a result of the implementation of these strategies is honesty, responsibility, and politeness.